(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Research looking at psychopathology in youth has archivedrates of disorders in children and adolescents approaching those present ingrown-up populations. For instance, information from the Great Smoky Mountains Studyof Youth demonstrate that 39.8% of the children in their sample met criteriafor a psychiatric diagnosis or practical weakness across any of their fouryearly time points (Farmer, Burns, Phillips, Angold, & Costello, 2003).